The Evidence Based Information Needs and Information Seeking Behaviours of Medical Faculty - Köse Uysal, Eda; Özenç Uçak, Nazan (Information World, 2013)
Today, it has become meaningless for physicians to decide diagnoses and therapeutics of diseases based only on experiences, it has elicited that the decisions should be backed up. Especially Evidence Based Medicine (EBM) practices replacing traditional medical practices require that diseases are supported with qualified and current researches in a systematic approach during the diagnosis and therapeutic processes in order to make correct decisions. Correspondingly, user studies on evidence based information needs and information seeking behaviours of the people working in medical sciences improve. This research aims to present evidence based information needs and information seeking behaviour features of medical academics and to specify similarities and differences between titles. In this research, carried out on a sample of 183 academics of 1053 academics working in Hacettepe University Faculty of Medicine, description method is used; questionnaire is used as data collection technique. As a result of the research, it is seen that there are similarities and differences between titles in evidence based information need and information seeking behaviour features. It is also stated that usage of evidence based resources differ by titles and medical academics need to be trained on EBM.